Replacement of a group of variables in trigonometric expression

I would like to make simplification of trigonometric expressions by using a replacement a group of variables.

Here the equation I have to simplify :

-Cos[γ[1][t] - θ[1][t] - ψ[1][t]] l[f] +
m[f] Sin[γ[1][t]] +
c[f] Sin[γ[1][t] - θ[1][t]] -
h[f] Sin[γ[1][t] - θ[1][t] - ψ[1][t]] +
x[P1][
t] == -Cos[γ[2][t] - θ[2][t] - ψ[2][t]] l[f] +
m[f] Sin[γ[2][t]] +
c[f] Sin[γ[2][t] - θ[2][t]] -
h[f] Sin[γ[2][t] - θ[2][t] - ψ[2][t]] +
x[P2][t]

For the simplification I also this equation

γ[1][t] - θ[1][t] - ψ[1][t] == γ[2][t] - θ[2][t] - ψ[2][t]

Consequently, I would like to replace only in the right hand side the group of variables γ[2][t] - θ[2][t] - ψ[2][t] by γ[1][t] - θ[1][t] - ψ[1][t]

After simplifications, I would like to obtain this equation :

m[f] Sin[γ[1][t]] + c[f] Sin[γ[1][t] - θ[1][t]] + x[P1][t] ==
m[f] Sin[γ[2][t]] + c[f] Sin[γ[2][t] - θ[2][t]] + x[P2][t]

Have you some ideas so to do this replacement γ[1][t] - θ[1][t] - ψ[1][t] == γ[2][t] - θ[2][t] - ψ[2][t] in the right hand side of my equation ?